1957
DOI: 10.1021/ja01574a070
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Steroids by Microorganisms. IV. 16α-Hydroxylation of 9α-Fluorohydrocortisone and 9α-Fluoroprednisolone by Streptomyces roseochromogenus

Abstract: productc is provided by the action of lithium aluminurn hydride on this intermediate \r.7 Acknowledgment.--The authors are grateful to Dr. H. T. Openshaw for a sample of isoemetine hydrobromide. Financial support was provided by the research committee of the Graduate School. f r o n s ) and similar ( c j . ref. 4) systems, catalytic reduction also afford? t h e more stable 3,15,20-cis-fvans product (E. E . van Tarnelen, 11. Shamma and P. E. Aldrich, TIIIS JCXJRXAI., 78, 4628 (195G). ( 7 ) I t is pertinent t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1959
1959
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The application of Zaffaroni-type systems to triaxpcinolone and related 16a-hydroxylated steroids has been described (4). The fortuitous similarity of papergram mobilities in several Bush-type systems of these two steroids is illustrated in Table I with systems I11 and IV. Using the six systems described in descending chromatography i t is possible to separate many derivatives of triamcinolone and many intermediates involved in the several reported syntheses (6,7). I n our hands modified Hush-type systems have been found to be more versatile in the complex separations involved in the production and analysis of triamcinolone than have the Zaffaroni-type systems.…”
Section: Paper Chromatography Qualitativementioning
confidence: 93%
“…The application of Zaffaroni-type systems to triaxpcinolone and related 16a-hydroxylated steroids has been described (4). The fortuitous similarity of papergram mobilities in several Bush-type systems of these two steroids is illustrated in Table I with systems I11 and IV. Using the six systems described in descending chromatography i t is possible to separate many derivatives of triamcinolone and many intermediates involved in the several reported syntheses (6,7). I n our hands modified Hush-type systems have been found to be more versatile in the complex separations involved in the production and analysis of triamcinolone than have the Zaffaroni-type systems.…”
Section: Paper Chromatography Qualitativementioning
confidence: 93%
“…Very recently Bracco et al showed that this enzyme can also hydroxylate five other steroids (pregnenolone, dehydroepiandrosterone, progesterone, ⌬ 4 -androstene-3,17-dione, and nandrolone) at the 16␣ position of the D ring (22). It is also noteworthy that in 1957, Streptomyces roseochromogenus was reported to hydroxylate two steroids (9␣-fluorohydrocortisone and 9␣-fluoroprednisolone) at the 16␣ position of the D ring (23), suggesting that S. roseochromogenus has a P450 that catalyzes a reaction similar to that of CYP154C5 of N. francinica. In fact, Berrie et al purified and characterized this P450 enzyme (24).…”
mentioning
confidence: 99%
“…Selective hydroxylation of the double bond at position 16 with osmium tetroxide in pyridinebenzene gives compound 127. The 9,11-double bond of this compound is converted to a 9α-fluoro-11β-hydroxyl group (128) by the method described for 9α-fluorocortisol (123) The 16α-hydroxyl group can also be introduced directly into 9α-fluoroprednisolone (124) by using a microbiological method originally developed by Squibb [253,254]. Triamcinolone 16α,17α-acetonide (130) is prepared by stirring a suspension of triamcinolone (129) in acetone in the presence of catalytic amounts of perchloric acid at approximately 20…”
Section: -Hydroxycorticosteroidsmentioning
confidence: 99%